A USB Kit for Digital I/O Applications in a Digital Electronics Lab Designed by Using PIC16C765 Microcontroller - BULDU, ALİ; KORKMAZ, HAYRİYE (WILEY, 2009)
In this article, a USB Kit is designed by using Microchip's PIC16C765 microcontroller that has a low-speed USB serial interface engine. It is used to communicate with and/or through USB port for digital I/O applications in a Digital Electronics Lab In this education kit, two groups of keys (switches) and a group of LED are used to realize the experiments about logic gate applications included in Electronics and Computer Education Department's curriculum of Marmara University and also included in other faculties' curriculums related to the engineering science all around the world. In designed board, one of the key groups is 8-bit software-controlled by using simulator interface and the other is 8-bit user-controlled by using real switches existing on the board. (C) 2008 Wiley Periodicals, Inc. Comput Appl Eng Educ 17: 131-138. 2009: Published online in Wiley InterScience (www.interscience.wiley.com): DOI 10.1002/cae.20172
Keywords: USB education kit; logic gates applications; PIC16F765